Polarimetric Reference Frames for Exoplanetary Atmosphere Characterization - Qadir, Y. A. (2025)
The characterization of exoplanetary atmospheres through polarimetric observations requires precise reference frames and ephemerides to accurately model the planet-star system. Upsilon Andromedae b, a hot Jupiter orbiting a main-sequence star, serves as an excellent test case for studying the role of reference systems in exoplanetary research. This work presents a refined approach to defining celestial reference frames for polarimetric studies, ensuring consistency with Earth-based and space-based observatories. We utilize time-resolved polarimetry to track the planet’s atmospheric scattering properties, necessitating rigorous alignment with the International Celestial Reference Frame (ICRF) and local terrestrial observatory frames. The impact of orbital ephemeris precision on derived polarization signals is explored, highlighting the need for updated planetary system parameters. Our study also addresses the transformation of reference systems to mitigate observational biases and improve consistency across different datasets. The findings demonstrate the importance of accurately calibrated reference frames in enhancing polarimetric measurements of exoplanets, with implications for future missions and ground-based monitoring programs. By integrating celestial reference systems with exoplanet observation techniques, we contribute to the broader effort of standardizing astronomical methodologies in planetary sciences.